Model-based calculating tool for pollen-mediated gene flow frequencies in plants. Issue 1 (30th December 2016) - Wang, Lei; Lu, Bao-Rong
Abstract : This study provide a model-based calculating tool/software that can accurately calculate pollen-mediated gene flow (PMGF) frequencies of wind-pollinated plant species by including five biological and climatic parameters. The calculating tool can easily be used by any users who are not familiar with mathematical modeling. The required parameters can be measured directly in the field without conducting PMGF experiments, which makes this tool practical to estimate PMGF frequencies. This tool will be helpful to estimate transgene flow and its potential impacts, in addition to determining isolation distances between GE and non-GE crops. Abstract : The potential social-economic and environmental impacts caused by transgene flow from genetically engineered (GE) crops have stimulated worldwide biosafety concerns. To determine transgene flow frequencies resulted from pollination is the first critical step for assessing such impacts, in addition to the determination of transgene expression and fitness in crop-wild hybrid descendants. Two methods are commonly used to estimate pollen-mediated gene flow (PMGF) frequencies: field experimenting and mathematical modelling. Field experiments can provide relatively accurate results but are time/resource consuming. Modelling offers an effective complement for PMGF experimental assessment. However, many published models describe PMGF by mathematical equations and are practically not easy to use. To increase the application of PMGF modelling for the estimation of transgene flow, we established a tool to calculate PMGF frequencies based on a quasi-mechanistic PMGF model for wind-pollination species. This tool includes a calculating program displayed by an easy-operating interface. Pollen-mediated gene flow frequencies of different plant species can be quickly calculated under different environmental conditions by including a number of biological and wind speed parameters that can be measured in the fields/laboratories or obtained from published data. The tool is freely available in the public domain (http://ecology.fudan.edu.cn/userfiles/cn/files/Tool_Manual.zip (14 December 2016)). Case studies including rice, wheat and maize demonstrated similar results between the calculated frequencies based on this tool and those from published PMGF data. This PMGF calculating tool will provide useful information for assessing and monitoring social-economic and environmental impacts caused by transgene flow from GE crops. This tool can also be applied to determine the isolation distances between GE and non-GE crops in a coexistence agro-ecosystem, and to ensure the purity of certified seeds by setting proper isolation distances among field production plots.